The Effect of Stoichiometry on Hydrogen Embrittlement of Ordered Ni3Fe Intermetallics - Y. X. Chen; Tao Chen; Haiyan Qian (Advances in Materials Science and Engineering)
The effects of Fe stoichiometry on hydrogen embrittlement and hydrogen diffusion in ordered Ni3Fe intermetallics were investigated. The experimental results show that the ordered Ni3Fe alloy with the normal stoichiometry has the lowest mechanical property, the highest susceptibility to hydrogen, and the highest ability of catalytic reaction. The mechanical properties, the susceptibility to hydrogen embrittlement, and the amount of adsorbed hydrogen of the ordered Ni3Fe alloy are dependent of degree of order of the alloy. The apparent hydrogen diffusion coefficient of the ordered Ni3Fe alloy is independent on degree of order of the alloy but depends on Fe stoichiometry. The activation energy of hydrogen diffusion decreased linearly with Fe stoichiometry for the ordered Ni3Fe alloy.